Innovative 3D printing technologies and advanced materials revolutionizing orthopedic surgery: current applications and future directions - Cong, Bo; Zhang, Haiguang (Frontiers in Bioengineering and Biotechnology, 2025)
Three-dimensional (3D) printing has rapidly become a transformative force in orthopedic surgery, enabling the creation of highly customized and precise medical implants and surgical tools. This review aims to provide a more systematic and comprehensive perspective on emerging 3D printing technologies—ranging from extrusion-based methods and bioink printing to powder bed fusion—and the broadening array of materials, including bioactive agents and cell-laden inks. We highlight how these technologies and materials are employed to fabricate patient-specific implants, surgical guides, prosthetics, and advanced tissue engineering scaffolds, significantly enhancing surgical outcomes and patient recovery. Despite notable progress, the field faces challenges such as optimizing mechanical properties, ensuring structural integrity, addressing regulatory complexities across different regions, and considering environmental impacts and cost barriers, especially in low-resource settings. Looking ahead, innovations in smart materials and functionally graded materials (FGMs), along with advancements in bioprinting, hold promise for overcoming these obstacles and expanding the capabilities of 3D printing in orthopedics. This review underscores the pivotal role of interdisciplinary collaboration and ongoing research in harnessing the full potential of additive manufacturing, ultimately paving the way for more effective, personalized, and durable orthopedic solutions that improve patient quality of life.